Green Synthesis and Characterization of Cinnamylideneacetophenone Compound Using Fe3O4 Magnetic as Catalyst - Dori Fitria; Antonius Herry Cahyana; Agus Rimus Liandi (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2021)
Cinnamaldehyde is a compound found in the skin of cinnamon plants which has various bioactivity. In this study, the compound cinnamaldehyde was modified with the help of Fe3O4 which was synthesized with the help of seaweed extract as a heterogeneous catalyst. Fe3O4-MNPs are synthesized using FeCl3 and Sargassum filipendula extracts as their natural reducing agents. The catalytic ability of Fe3O4 was evaluated in the reaction between cinnamaldehyde and aromatic ketone compounds synthesized by the reflux method. Structure Analysis and elucidation of the synthesized compounds were carried out by measuring the vibrations of the functional groups by FTIR, and the determination of H and C atoms by HNMR and CNMR analysis. The FTIR, proton and carbon NMR analysis have identified that the synthesized product was cinnamylideneacetophenone by the name 1,5-diphenylpyenta-2,4-dien-1-one. The optimum conditions were obtained at a catalyst concentration of 10% w/w for five hours with a yield of 36%. The yield of this reaction was better than the reaction without a catalyst.